1998
DOI: 10.1523/jneurosci.18-16-06466.1998
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Trigeminal Brainstem Interneurons Form Subpopulations to Produce Different Forms of Mastication in the Rabbit

Abstract: To determine how trigeminal brainstem interneurons pattern different forms of rhythmical jaw movements, four types of motor patterns were induced by electrical stimulation within the cortical masticatory areas of rabbits. After these were recorded, animals were paralyzed and fictive motor output was recorded with an extracellular microelectrode in the trigeminal motor nucleus. A second electrode was used to record from interneurons within the lateral part of the parvocellular reticular formation (Rpc-␣, n ϭ 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 58 publications
4
76
1
Order By: Relevance
“…Our data are concordant with the conclusions of most physiological studies, which showed that the latencies of vestibular-elicited masseter muscle responses are too long for these responses to be mediated through direct connections between the VN and Mo5 (Tolu and Pugliatti 1993;Tolu et al 1994Tolu et al , 1996Deriu et al 1999). Potential relays from the VN and PH to masseter motoneurons could include several regions of the pontomedullary reticular formation, particularly the reticular zone surrounding the Mo5, which has been reported to contain neurons that are components of the network responsible for the generation of rhythmic jaw movements (Donga and Lund 1991;Inoue et al 1992;Westberg et al 1998) and to be involved in modulating trigeminal motoneuron activity induced by peripheral and cortical inputs (Sessle 1977;Nozaki et al 1986 a,b;Westberg and Olsson 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are concordant with the conclusions of most physiological studies, which showed that the latencies of vestibular-elicited masseter muscle responses are too long for these responses to be mediated through direct connections between the VN and Mo5 (Tolu and Pugliatti 1993;Tolu et al 1994Tolu et al , 1996Deriu et al 1999). Potential relays from the VN and PH to masseter motoneurons could include several regions of the pontomedullary reticular formation, particularly the reticular zone surrounding the Mo5, which has been reported to contain neurons that are components of the network responsible for the generation of rhythmic jaw movements (Donga and Lund 1991;Inoue et al 1992;Westberg et al 1998) and to be involved in modulating trigeminal motoneuron activity induced by peripheral and cortical inputs (Sessle 1977;Nozaki et al 1986 a,b;Westberg and Olsson 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Dual-referent phase analysis relates phase to function more precisely than single-referent phase analysis for rhythmic motor patterns in which duty cycle varies substantially (Berkowitz and Stein 1994). Dual-referent phase analysis is now conventionally used to analyze turtle scratching and swimming and has also been used to analyze rabbit mastication (Westberg et al 1998), neonatal rat locomotor rhythms Kiehn 1999, 2000), neonatal mouse locomotor-like activity (Kwan et al 2009;Nishimaru et al 2006;Zhong et al 2006aZhong et al , b, 2007Zhong et al , 2010Zhong et al , 2011, human walking (Reisman et al 2005), and leech crawling and swimming (Briggman and Kristan 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the supraV may be a key structure for the induction of RJMs. It should also be noted, however, that, together with the supraV, the dorsal part of the principal sensory trigeminal nucleus (Tsuboi et al, 2003), the oral subnucleus of the spinal trigeminal nucleus, and the interV adjacent to this subnucleus (Inoue et al, 1994;Westberg et al, 1998) contain many neurons of which unit activities are synchronized with the jawclosing or jaw-opening phase during fictive mastication induced by cortical stimulation.…”
Section: Cortico-tegmental Projections From Jaw Movement-related Areasmentioning
confidence: 99%